Menolak Intervensi Pengiklan sebagai Pertahanan Independensi Bocor Alus Politik - Jacinda Claramuti Purnomo; Maimon Herawati; Achmad Abdul Basith (Institut Nalanda, 2026)
The financial sustainability of the media in Indonesia relies heavily on advertising as its primary source of revenue. This dependence puts editorial independence in a difficult position, as the advertiser is the very same entity that is the subject of the news coverage. This study examines how Bocor Alus Politik resists advertiser interference as a means of defending its editorial independence. Using a qualitative approach with a case study design, data was collected through in-depth interviews with the managing editor, producers, journalists, and the business team, and supplemented by document analysis. The analysis is grounded in the five principles of public service (independence) by Kovach & Rosenstiel (2001) and the concept of the dual product market by Robert G. Picard (1989). The findings indicate that Bocor Alus Politik’s defense of its independence operates on multiple levels: a structural separation between the editorial and business teams that is internalized as a collective value across divisions; strict selection of potential collaboration partners; editorial control over content substance without exception; and public transparency through explicit disclaimers on collaborative content.